Biopsychosocial Correlates of Presence and Intensity of Pain in Adolescents With Inflammatory Bowel Disease - Murphy, Lexa K.; Rights, Jason D.; Ricciuto, Amanda; Church, Peter C.; Ahola Kohut, Sara (Frontiers in Pediatrics, 2020)
Background:There is growing consensus that pain in pediatric inflammatory bowel disease (IBD) is not fully explained by disease-related processes. However, previous studies have largely measured individual biological, psychological, or social risk factors for pain in isolation. Further, not all youth with IBD presenting to clinic will report presence of pain, and those who do vary in their reports of pain intensity. This study therefore extends prior research by determining biopsychosocial correlates of both presence and intensity of pain in adolescents with IBD, in order to inform targeted pain management intervention approaches. Methods:Adolescents with IBD followed at SickKids, Toronto, and their parents were consecutively enrolled from outpatient clinic. IBD characteristics (diagnosis, time since diagnosis, patient-reported disease activity) were collected. Adolescents reported on current pain (NRS-10), internalizing symptoms (Strengths and Difficulties Questionnaire), and pain catastrophizing (Pain Catastrophizing Scale-Child). Parents reported on protective responses to child pain (Adult Responses to Child Pain) and pain catastrophizing (Pain Catastrophizing Scale-Child). Hurdle models were conducted to examine predictors of presence and intensity of pain in the same model. Biological (patient-reported disease activity, IBD diagnosis subtype, illness duration), psychological (internalizing symptoms, pain catastrophizing) and social (parent pain catastrophizing, parent protective responses) factors were entered as predictors, adjusting for age and sex. Results:Participants included 100 adolescents (12-18; Mean=15 years) with IBD (60% Crohn’s Disease, 40% Ulcerative Colitis or IBD-unclassified) and 76 parents. The majority of the sample was in clinical remission or reported minimal symptoms. Half of participants reported no current pain; for those reporting pain, intensity ranged 1-7 (M=3.43, SD=1.98). Disease activity (OR=53.91,p<.001) and adolescent internalizing symptoms (OR=7.62,p=.03) were significant predictors of presence of pain. Disease activity (RR=1.37,p=.03) and parent protective responses (RR=1.45,p=.02) were significant predictors of intensity of pain. Conclusions:Results suggest that the experience of pain in pediatric IBD is biopsychosocially determined. Patient-reported disease activity and internalizing symptoms predicted presence of pain, while disease activity and parent protective responses predicted intensity of pain. While medical intervention in pediatric IBD is focused on disease management, results suggest that depression/anxiety symptoms as well as parent protective responses may be important targets of pain management interventions in pediatric IBD.